AGE ORIENTATION OF WELFARE STATES IN CENTRAL AND EASTERN EUROPE: A COMPARATIVE ANALYSIS OF POLAND AND HUNGARY - Mackevičiūtė, Raimonda (Politologija, 2016)
This article analyses age orientation of welfare states in CEE countries. In the context of the current demographic changes, how the welfare states address the risks faced by people at different stages in the life course affects both citizens’ lives and the capacity of national economies to adapt to new conditions. For this reason, it is becoming more and more important to evaluate what different welfare states do to ensure welfare of their elderly and young citizens. With few exceptions, there is very little comparative evidence on the age orientation of social policies in OECD countries – and none in Central and Eastern Europe (CEE) countries. Age orientation of welfare states in this region is analysed for the first time in this article. Age orientation is measured by calculating the Elderly/Children Spending Ratio (ECSR). It discloses significant differences of social policies’ age orientation among CEE countries. Two of the most exceptional cases are Poland and Hungary. Welfare state’s age orientation of these similar countries is completely different. Social policy of Poland is elderly- oriented, while social policy of Hungary is youth- oriented. Therefore, the purpose of this research is to explain what determines the differences of the welfare states age orientation in Poland and Hungary. This article analyses the formation process of welfare states’ age orientation in Poland and Hungary from the perspective of new institutionalism, namely historical institutionalism. Partisan competition and fragmentation of the social system are two main institutions that have determined age orientation of welfare states in Poland and Hungary. A comparative systemic process analysis reveals that welfare states’ age orientations of Poland and Hungary are determined by two historical critical junctures. Firstly, the weak communist party in Poland sought for political support of narrow groups. It caused the creation of special pensions privileges and the pension system fragmentation. For this reason, public pension spending was higher than spending for children and families – Poland became oriented towards the elderly. In Hungary, the communist party was stronger; therefore, there was no reason for creating special pensions privileges. In Hungary, spending for families and children was generous – it became youth oriented. The second critical juncture occurred during the first years of transition. The partisan competition of Poland was especially fragmented, so it was important for parties to get political support of particular groups. For this reason, parties increased the pension system fragmentation by creating new and maintaining old pensions privileges. Extremely expanded pension spending was partly financed by diminished spending for families and children – Poland’s welfare state’s age orientation towards the elderly was significantly strengthened. The partisan competition of Hungary was stronger; therefore, it remained youth oriented. After that, welfare states’ age orientation of these two countries followed the same path.